2023
DOI: 10.3390/polym15204044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cooling Efficiency of Polymer Injection Molds by Computer Simulation Using Conformal Channels

Carlos Vargas-Isaza,
Adrian Benitez-Lozano,
Johnnatan Rodriguez

Abstract: Injection molds are production tools that require detailed analysis based on the quality of the resulting part, the impact on cycle times, and the expected production volume. Cooling channels also play a critical role in mold performance and product quality as they largely determine cycle time. Designs that incorporate conformal cooling channel (CCC) geometries that conform to or align with the part contour are currently being explored as an alternative to conventional cooling channel designs in injection mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Vargas-Isaza et al [ 7 ] evaluated the cooling efficiency of polymer injection molds with CCC using a numerical simulation. The results showed that a 9.26% reduction in the warpage of the cup-shaped injection molded part was obtained using a CCC compared with the conventional cooling channel.…”
Section: Introductionmentioning
confidence: 99%
“…Vargas-Isaza et al [ 7 ] evaluated the cooling efficiency of polymer injection molds with CCC using a numerical simulation. The results showed that a 9.26% reduction in the warpage of the cup-shaped injection molded part was obtained using a CCC compared with the conventional cooling channel.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Nguyen et al [7], CC was designed Polymers 2024, 16, 874 2 of 17 to enhance temperature distribution on the mold cavity surface during the injection molding process, demonstrating that the average temperature of the mold cavity surpassed that achieved with a conventional straight cooling channel. Vargas-Isaza et al [8] assessed the cooling efficiency of polymer injection molds employing CC via numerical simulation. The results indicated a 9.26% reduction in warpage for the cup-shaped injection-molded part when CC was used, as opposed to the conventional cooling channel.…”
Section: Introductionmentioning
confidence: 99%